PENGARUH KENAIKAN INVESTASI SWASTA DAN PENGELUARAN PEMERINTAH DAERAH TERHADAP KETIMPANGAN PEMBANGUNAN DI KALIMANTAN BARAT - Heny Sucihati, B61109044 (Jurnal Ekonomi Daerah (JEDA), 2016)
ABSTRACKThe effect of rising private investment and government expenditure AgainstInequality Regional Development In Kalimantan BaratThis study aims to examine the implementation of the Kuznets curve"U upside", and analyze the effect of government investment and expenditureon the level of economic inequality that occurred in Kalimantan BaratProvince in the period 1990 to 2010. The research technique used is throughdescriptive analysis and quantitative approach. Descriptive approach based ondata from secondary data, journals, articles, literature and previous researchrelated to the problems. A quantitative approach based on econometricanalysis using multiple linear regression.The data used in this research is secondary data comprising time seriesdata from 1990 to 2010 were obtained from the BPS, BPS Kalimantan BaratProvince, Badan Penanaman Modal Daerah (BPMD) and outcomes researchprevious.The results obtained are variable private investment and significantnegative effect on Î± = 5%, the variable investment and significant negativeeffect on Î± = 5% of the development gaps in the Kalimantan Barat Province.Meanwhile, government spending and a significant positive effect. CalculatedF value of 15.534 with probability 0.0000 smaller than Î± = 5%, so itconcluded that two independent variables, namely private investment andgovernment spending jointly affect the level of development gaps in the regionof Kalimantan Barat ProvinceKeywords: Inequality Development, Kuznets hypothesis, Private Investment,and Government Spending